Application of Ammonium Carbonate Solutions in Electrochemical Technology of Heavy Alloy Waste Processing (Global Journal of Science Frontier Research, 2021)
The electrochemical behavior of the VNZhK alloy waste (wt.%: W 90, Ni 7,2, Fe 1,8, Co 1) in a solution of (NH 4 ) 2 CO 3 1M was investigated by using the methods of cyclic voltammetry in the potentiodynamic mode, potentiostatic electrolysis and electrolysis under the action of alternating current (industrial frequency 50 Hz). It was found, that the highest oxidation rate of VNZhK alloy waste (1700 mg /cm 2 •h) is achieved by using alternating current, and the highest current efficiency (about 100%) -by using direct current. A technological scheme was proposed for recovery of tungsten from the heavy tungsten alloy waste in the form of ammonium paratungstate.
Keywords: the methods of cyclic voltammetry in the potentiodynamic mode